The accuracy of biomechanical mechanisms for dental deep bite correction using the Invisalign system - Fiorillo Gianluigi; Campobasso Alessandra; Garrisi Lorenzo; Battista Giovanni; D’Antò Vincenzo; Mandelli Alice; Mandelli Gualtiero; Ambrosi Alessandro; Gastaldi Giorgio (Australasian Orthodontic Journal)
To evaluate the accuracy of the Invisalign appliance in correcting an anterior deep bite in adults and to compare different mechanisms of bite opening.